Literasi Digital dalam Meningkatkan Mutu Pembelajaran di MTs Yogyakarta - Syahadah, Tinta Merry; Hidayati, Dian (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2024)
The purpose of this research is to describe digital literacy learning in Madrasah Tsanawiyah schools. Participants consisted of teachers and students (MTs) Muallimat Muhammadiyah Ypgyakarta Madrasah. Efforts to improve the quality of learning. This type of research is descriptive qualitative research or research that describes digital literacy in relation to the quality of learning at Madrasah Tsanawiyah to improve the quality of learning. Based on the results of the study, digital literacy applied in Madrasah Tsanawiyah can improve the quality of student learning in general.